Students’ descriptions about experiences beneficial to mental health - a thematic analysis - Anne Skoglund; Sarah Hotham; Agneta Schröder; Øyfrid Larsen Moen (BMC Public Health)
Abstract University years are an important transitional time for young adults. Recently, an increasing number of students have reported mental health problems. The increasing numbers are an international phenomenon. Qualitative research on mental health promotion for students is, however, scarce. The aim of this study is to explore students’ descriptions of experiences in their student life that are beneficial to mental health. A Norwegian project named “In my experience” collected descriptions, through the web-based tool Sensemaker, from students about experiences that have had an impact on their student life. This study explores the descriptions of experiences beneficial to students’ mental health that the students categorized as having had a positive or very positive impact on their student life. A total of 171 descriptions from students aged 18–29 were analyzed using thematic analysis. Two main themes were identified: becoming a student, which consisted of descriptions about the feeling of a new life as a student, and being a student, which described experiences with managing student life that were beneficial for mental health. Experiences such as being welcomed, being included, belonging to a social group, finding one’s own identity, maturing, and developing were all highlighted in the descriptions. Student societies and other forms of civic engagement and being accepted and included in an academic community were fundamental. A limitation of the study was the relatively low number of male participants, and further research on male students’ descriptions about beneficial experiences is needed.